Toward an Inclusive Framework for Remote Musical Education and Practices - Cristina Rottondi; Matteo Sacchetto; Leonardo Severi; Andrea Bianco (IEEE Access)
This paper provides an overview on inclusiveness in remote music education and networked music performances, highlighting issues and difficulties encountered by users with visual, auditory or motor disabilities when approaching such practices. Audio-visual tools, motion tracking systems, immersive audio and haptic feedback technologies that can be leveraged to enhance the accessibility of web-based platforms for online music teaching and remote performances are analyzed and classified. Moreover, the manuscript discusses the integration of such technological solutions in a networked music performance framework and their potential benefits for various categories of disabled users, describing some exemplary use-cases. Finally, open technical challenges for the practical realization and deployment of such a framework are identified, as well as future research directions towards its incorporation within the so-called Musical Metaverse.